Influence of binder in the drying shrinkage of fiber cement - Giordano, Brunoro Leite (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
There has much interest in the fiber cement industry in improving binder composition in order to achieve better economic, technical and environmental results. In this context, cements with lower clinker content are an attractive alternative and have already been used by the industry. However, fibercement sheets reinforced with organic fibers frequently present edge cracks resulting from drying the components in stockpiles. This study evaluates the impact of partially replacing clinker by blast furnace slag activated with sodium silicate on the mechanical properties, porosity, hydrated phases, and drying shrinkage of fiber cement reinforced with organic fibers. Samples were produced with commercial Brazilian CPII F-32 cement and also with a mixture of CPII F-32 with granulated blast furnace slag activated by sodium silicate. The results show that replacing clinker by slag activated by sodium silicates increases the amount of pores smaller than 0.003 ?m, due to an increase in the amount of CSH formed in hydration. Consequently, samples produced with CPII F-32 mixed with slag and sodium silicate present much higher drying shrinkage.